E-100 Use of the 0.027 VIA Microcatheter for Pipeline Embolization of Cerebral Aneurysms: A Technical Note. (29th July 2016) - Lin, L; Colby, G; Xu, R; Bender, M; Jiang, B; Lubelski, D; Coon, A
Abstract : Introduction: Pipeline embolization devices (PEDs) are designed for delivery through a 0.027" microcatheter such as the Marksman (Medtronic). Challenges with second generation FlexPEDs include limited support from the Marksman for consistent resheathing and providing enough push for delivery. The VIA27 (Sequential) is an alternative 0.027" microcatheter originally designed for intrasaccular flow diverter delivery. Here we describe our experience with the VIA27 in the delivery of PEDs. Methods: We retrospectively identified patients who underwent PED treatment with the VIA27 microcatheter at our institution. Patient demographics, equipment utilized, intraprocedural catheter positions and periprocedural complications were documented. Results: 36 patients underwent 40 embolizations of 44 aneurysms with 48 PEDs (Table 1 ) using the VIA27. The average age was 59.9 ± 11.0 years; 7 (17.5%) were male. Most aneurysms 41 (93.2%) were located anteriorly. The average aneurysm size was 7.2 mm with 38 (86.4%) small, 3 (6.82%) large, and 3 (6.82%) giant. The VIA27 was successfully used to deploy all 48 PEDs (Figure 1 ). 6 attempts were made to resheath the PED during placement; all were successful. The distal tip of the catheter was located in the ACA 4 (10%), MCA 32 (80%), supraclinoidal ICA 1 (2.5%), basilar 2 (5%), and distal vertebral 1 (2.5). In 3 (7.5%) cases where the VIA27 catheter was unable to track, alternate catheters were used to advance and then exchanged back to the VIA27. In 3 (7.5%) instances, the Marksman was unable to provide adequate push for PED deployment; the VIA27 was exchanged for placement of the PED. No patients experienced iatrogenic vessel injury or other microcatheter associated complications. Conclusions: The VIA27 is capable of safe FlexPED delivery in the treatment of intracranial aneurysms. We have shown its utility in enhancing both resheathing and push for optimal FlexPED placement. The 0.027" VIA may be a useful and safe adjunct to the more traditional Marksman in FlexPED treatments of cerebral aneurysms. Disclosures: L. Lin: None. G. Colby: None. R. Xu: None. M. Bender: None. B. Jiang: None. D. Lubelski: None. A. Coon: None.